Pengaruh Kepuasan Kerja, Motivasi, Dan Komitmen Organisasi Terhadap Kinerja Karyawan - Rostini, Rostini; Nasir, Muhammad (Movere Journal, 2024)
This research aims to examine the influence of job satisfaction, motivation and commitment on employee performance at the University of Eastern Indonesia as many as 105 people using the correlation analysis method. This research found that there is a significant influence of job satisfaction, motivation and organizational commitment on employee performance. The largest correlation occurs between motivation and performance at 0.973, then the second correlation occurs between the relationship between job satisfaction and performance at 0.507, and the third correlation is organizational commitment to performance at 0.492. Overall, all independent variables, namely job satisfaction, motivation and organizational commitment, have a positive and significant influence on employee performance.